Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/brs.0000000000004418
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis as a Risk Factor for Intraoperative Complications and Long-term Instrumentation Failure in Patients With Scoliotic Spinal Deformity

Abstract: Study Design. A retrospective review study. Objective. This study aims to determine the effect of osteoporosis on spine instrumentation. Summary of Background Data. Osteoporosis is a common skeletal pathology that affects systemic cortical bone maintenance and remodeling. This disease accelerates the degeneration of the spine, often necessitating spinal surgery for progressive vertebral deformity, pathologic fracture, bony canal stenosis, and/or neural element decompression. There is a paucity of literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…In addition, due to the placement of the 2 screws and cage of the ZPSC implants, the cage placed in front of the intervertebral space can act as the fulcrum of the mechanics. This may produce a forward traction to the superior and inferior vertebrae and can increase the incidence of cage subsidence 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to the placement of the 2 screws and cage of the ZPSC implants, the cage placed in front of the intervertebral space can act as the fulcrum of the mechanics. This may produce a forward traction to the superior and inferior vertebrae and can increase the incidence of cage subsidence 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The case underscores a significant challenge of late referral to neurosurgery following an extended period of TB treatment. Despite the successful management of TB, the patient's persistent axial pain led to prolonged immobilization, likely contributing to the development of severe osteoporosis, as indicated by a t-score of -5.7 on bone densitometry -a factor well-documented to have a substantial impact on surgical outcomes [5][6][7]. Osteoporosis, characterized by reduced bone mineral density, introduces an elevated risk of implant failure following spinal procedures, particularly in regions like the lumbosacral junction, which demands substantial mechanical stability [5].…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al and Mugge et al reported that the incidence of implant-related complications and rate of re-operations were increased by osteoporosis as a complication after correction and fixation in adult spinal deformities [31,32]. Khalid et al and Wolfert et al reported that osteoporosis may be an adverse prognosis factor for post-operative implant-related complications and other conditions even after short fusion [33,34].…”
Section: The Relationship Between Screening Tests and History Of Oste...mentioning
confidence: 99%